Hubungan konsumsi snack, menyikat gigi dan kunjungan dokter gigi terhadap karies pada siswa kelas VII SMP Santo Yoseph Denpasar - Patricia Eviana Cahyadi; Steffano Aditya Handoko; Ni Wayan Arya Utami (Intisari Sains Medis, 2018)
Introduction : Dental caries is the most prevalent oral disease in Indonesia that could occur in all age groups. According to the WHO, about 60 - 90% school children worldwide have dental caries. The aims of this study were to analyze the correlation between snacking (consumption of snacks or sweetened drink), tooth brushing habit and dental visit with caries incidence.Method: Study design using a cross-sectional analytical study, sampled from one hundred and two seventh grade Santo Yoseph junior high school students. Samples were chosen using purposive random sampling. The data was analyzed using descriptive method and risk estimate with chi-square test.Result: The prevalence of caries observed in the samples was 52.0%. The results was statistically significant for correlation between tooth brushing habit and caries incidence (p= <0.001; OR= 7.44; CI 95%= 2.71 – 20.42). Consumption of snacks or sweetened drink (p= 0.25; OR= 1.58; CI 95%= 0.71–3.50) and dental visit (p=0.903; OR= 1.502; CI 95%= 0.46–2.37) were not statistically significant with caries incidence.Conclusion: Tooth brushing habit was concluded as the most significant factor in dental caries incidence. It is recommended for school to educate the student about how to brushing teeth properly in collaboration with the primary health care centers.